Objective psychosocial function vs. subjective quality-of-life in schizophrenia within 5-years after diagnosis: A study from southern India. (February 2019) - Kurtz, Matthew M.; Gopal, Subhashini; John, Sujit; Thara, R.
Highlights: Subjective quality of life (QOL) and psychosocial function was studied in early schizophrenia in India. Symptoms were the best predictor of both subjective QOL and objective functioning. Negative symptoms were linked to objective psychosocial function only. Depression and cognition were also linked to sQOL but not objective function. Abstract: There is increasing interest from treaters and patients alike in subjective quality-of-life (sQOL) and objective psychosocial function as indices of treatment outcome in studies of schizophrenia. With the emergence of evidence-based treatment protocols (e.g., NIMH-funded Recovery after Initial Schizophrenia Episode Initiative) these outcomes are of particular significance in treatment studies of samples early in the course of their illness. Few studies have investigated demographic, clinical and cognitive factors associated with sQOL in samples early in the course of their illness and compared these factors to objective measures. We administered measures of sQOL or satisfaction with life, and objective psychosocial function to 59 people with schizophrenia within 5-years of diagnosis, along with standardized measures of symptoms and cognition. Results revealed that symptoms, rather than cognitive or demographic variables, were the best independent predictors of both subjective QOL and objective functioning. Positive symptoms were independent predictors of sQOL, while positive and negative symptoms were independent predictors of objective psychosocial status. Depression and cognition were also linked to sQOL. These findings point to the importance of attending to residual positive symptoms early in the treatment of schizophrenia as a means of possibly enhancing both subjective and objective outcome in early course schizophrenia.